Development of thermoelectric semiconductor devices for medical applications - M. A. Khazamova (Вестник Дагестанского государственного технического университета: Технические науки)
Aim. To analyse the prospects of developing and applying thermoelectric semiconductor energy converters in medicine. Methods. The research was based on theoretical and experimental achievements in the field of creating devices producing thermal effects on individual areas of the human body. Results. Fundamentally new devices with different thermal schemes based on thermoelectric semiconductor converters were created for diverse medical applications. A number of theoretical and experimental works were conducted to create a theoretical basis for the proposed devices. The prospects of developing and applying thermoelectric semiconductor heat devices in medicine were considered. The design of devices for providing thermal influence on individual areas of the human body was described. Conclusion. The developed thermoelectric semiconductor devices and devices for producing local thermal effects on individual organs of the human body ensure their use in medical practice due to simplicity and reliability.